Quantitative assessment of beta radiation shielding in medical polymers based on Monte Carlo simulations - Ayar, Kevser Hisiroglu; Akcali, Ozgur; Toker, Ozan; Icelli, Orhan (PERGAMON-ELSEVIER SCIENCE LTD, 2026)
The radiation resistance and sterilization performance of polymeric materials are critical in medical and pharmaceutical technologies. This study provides a quantitative assessment of beta-particle attenuation in five medical-grade polymers (PS, PET, PVC, PVDC and PVT) using Monte Carlo (MCNP6.2) simulations. Seven beta-emitting isotopes (H-3, Ni-63, C-14, Pm-147, Tc-99, Sr-90, and Y-90) were considered to cover an energy range from 5.7 keV to 2.28 MeV. The transmission-thickness relationship is described using logarithmic regression (R-2 > 0.99), and the Half Absorption Thickness (HAT) is evaluated as a compact metric of shielding performance. The results reveal a strong correlation between polymer chemistry and attenuation behavior. Halogenated polymers (PVC and PVDC) exhibit the lowest HAT values and strongest attenuation at medium and high energies, whereas hydrocarbon-based PS and PVT show greater transmission and reduced energy absorption. PET demonstrates an intermediate behavior, balancing transparency with moderate attenuation capability. HAT values extend across two orders of magnitude, from similar to 1.4 x 10(-7) m for low-energy H-3 to similar to 9.2 x 10(-5) m for high-energy Y-90, highlighting the strong impact of beta energy. The findings provide quantitative guidance for the selection and design of polymeric shielding layers in radiation-exposed medical components, radiopharmaceutical packaging, or sterilization systems.
Keywords: Beta radiation; Medical polymers; Monte Carlo simulation; Radiation sterilization; Beta shielding; Chemistry; Nuclear Science & Technology; Physics